Murder runs in the family - Berry, Tamara (Poisoned Pen Press, 2025)
"Amber Winslow's life has taken a serious turn for the worse. When an impulsive decision forces her to flee her former life carrying nothing but the clothes on her back, she heads to the sunny state of Arizona...and to the luxury accommodations of her grandmother's retirement community. But as soon as she sneaks her things into Seven Ponds-a place she technically doesn't qualify for and definitely can't afford-she finds that her Grandma Jade is about to be arrested for murder. With the help of the other retirees and her grandma's true crime podcast friends, Amber must work to find the real killer"--